Tanggung Jawab Keperdataan Orang Tua Terhadap Anak-Anak Pasca Pereceraian di Wilayah Gorontalo (Penyuluhan Di Desa Kaaruyaan Kecamatan Mananggu Kabupaten Boalemo) - Dolot Alhasni Bakung; Zamroni Abdussamad; Mohamad Hidayat Muhtar; Apripari Apripari; Zainal Hadju (Universitas Katolik Widya Karya Malang, 2023)
Legal counseling can be done through community empowerment which is one of the efforts made by lecturers at the Faculty of Law, Gorontalo State University in understanding legal knowledge to the community, including about, parents' civil responsibility for post-divorce in Kaaruyaan Village, Mananggu District, Boleoa Regency. Legal prohibition for violations of non-fulfillment of children's rights after divorce often occurs in a number of areas including in some villages where this is caused by ignorance of the community in general and parents are concerned about what are the rights and obligations of parents to children after divorce where the case is mostly dominated by fathers as insurers who have not fulfilled their obligations as fathers, Especially when the father re-married another woman. So the impact of empowering this legal counseling is the independence and understanding of the community in overcoming their legal problems through community initiatives and creativity and village officials assisted by lecturers in the environment of the Faculty of Law, Gorontalo State University. Of course, it requires people who are willing and able and have the knowledge, skills and attitudes to get out of their problems. This paper uses the quality descriptive method, in this case the descriptive analysis will discuss the condition of partners regarding understanding of the law. While quantitative analysis is carried out to calculate the feasibility of legal settlements carried out by partners. The result of this discussion is that with the growing understanding of law, the pillars of justice and expediency must be accompanied by efforts to foster and develop to legal counseling so that it becomes a law-conscious, independent and sustainable society.